2023
DOI: 10.1071/hc23082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how a patient encounter tracking and learning tool is used within general practice training: a qualitative study

Michael Bentley,
Jennifer Taylor,
Alison Fielding
et al.

Abstract: Introduction In Australian general practitioner (GP) training, feedback and reflection on in-practice experience is central to developing GP registrars’ (trainees’) clinical competencies. Patient encounter tracking and learning tools (PETALs) that encompass an audit of consecutive patient consultations, feedback, and reflection are used to determine registrars’ in-practice exposure and have been suggested as a tool for learning within a programmatic assessment framework. However, there is limited qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…They found that ReCEnT can prompt self-reflection among registrars, leading to changes in clinical practice, learning approaches and training plans. Bentley and colleagues 8 build on these survey findings 7 by using qualitative methods to further explore participants' perceptions of ReCEnT's utility. They conclude that for ReCEnT to achieve its goal of being an assessment for learning (as opposed to an assessment of learning) requires effective engagement between registrars, their supervisors and medical educators.…”
Section: Doing the 'Bread And Butter' Of General Practice Well In Unc...mentioning
confidence: 99%
“…They found that ReCEnT can prompt self-reflection among registrars, leading to changes in clinical practice, learning approaches and training plans. Bentley and colleagues 8 build on these survey findings 7 by using qualitative methods to further explore participants' perceptions of ReCEnT's utility. They conclude that for ReCEnT to achieve its goal of being an assessment for learning (as opposed to an assessment of learning) requires effective engagement between registrars, their supervisors and medical educators.…”
Section: Doing the 'Bread And Butter' Of General Practice Well In Unc...mentioning
confidence: 99%